Effectiveness of placement of second miniplates as tension band unit in mandibular parasymphysis fractures - Javad Yazdani; MohamadAli Ghavimi; Mahsa Taghizadeh; Yousef Kananizadeh; Milad Ghanizadeh (Wolters Kluwer Medknow Publications, 2019)
Background: The ideal position of the plates and the need for additional plates are discussed continuously. In mandible, the tensile forces at the fracture line should be neutralized with a tension band. This study evaluated the role of the mandibular arch bar as a tension band eliminating the need for an upper miniplate (tension band plate) in cases of parasymphysis fractures. Materials and Methods: In this randomized control trial, a total of 90 patients with mandibular parasymphysis fractures underwent treatment in two groups. Group A was treated with one titanium miniplate along with Erich's arch bar. In Group B, two titanium miniplates were placed across the fracture site along with Erich's arch bar. Then, the complications and duration of the operation time were compared between two groups. The results were considered statistically significant when the P < 0.05. Results: No significant difference was observed between the groups regarding postoperative complication rate. 1 month after surgery in Group A, number of patients with sensory impairment (17%) was significantly lower than Group B (37%) (P = 0.029). Furthermore, the operation time of Group A was significantly shorter than Group B (P < 0.001). Conclusion: In the presence of arch bar, placing one miniplate instead of the routine technique of placing two, do not increase complication rates. Furthermore, it reduces the operation time and costs and results in a better neurosensory recovery outcome in short time.